Kontestasi antar orang asli Papua terhadap hak pertuanan di Kaimana - Cahyo Pamungkas (Masyarakat, Kebudayaan dan Politik, 2016)
This article is addressed to describe the social relations within the Papuan ethnic groups and between Papua native and migrants concerning some customary rights in Kaimana district. This research describes the struggle of inland and beach tribes in fighting for customary rights of land in Kaimana. Moreover, it captures the respond of migrants in dealing with the customary right. This study shows the recognition of the the eldest ethnic in Kaimana is a strategy and discourse constructed by Papua ethnic groups that have felt marginalized while migrants have taken their resources. This right could be understood as the need for recognition of Papua ethnic groups. The most important issue is not who the native of Kaimana is, but what the proper ways to give recognition to Papua ethnic groups which had been left behind in development are. The relation between the Papua natives and migrants in Kaimana is not complicated as the migrants have no privileges in the political contestation. However, these relationship are affected by the differences in religious affiliations. The Muslim Papua ethnic groups generally have a closer relationship with the Muslim migrants. The analytical framework of this study using the theoretical framework of identity and ethnicity to look at the issue. Does the definition of identity and ethnicity according to sociological theories are still relevant to understanding the issue of claims of ethnic identity in the city of Kaimana.